Human SIRT2 and SIRT3 deacetylases function in DNA homologous recombinational repair. (18th March 2021) - Yasuda, Takeshi; Takizawa, Kazuya; Ui, Ayako; Hama, Michio; Kagawa, Wataru; Sugasawa, Kaoru; Tajima, Katsushi
Abstract: SIRT2 and SIRT3 protein deacetylases maintain genome integrity and stability. However, their mechanisms for maintaining the genome remain unclear. To examine the roles of SIRT2 and SIRT3 in DSB repair, I‐SceI‐based GFP reporter assays for HR, single‐strand annealing (SSA) and nonhomologous end joining (NHEJ) repair were performed under SIRT2‐ or SIRT3‐depleted conditions. SIRT2 or SIRT3 depletion inhibited HR repair equally to RAD52 depletion, but did not affect SSA and NHEJ repairs. SIRT2 or SIRT3 depletion disturbed the recruitment of RAD51 to DSB sites, an essential step for RAD51‐dependent HR repair, but not directly through RAD52 deacetylation. SIRT2 or SIRT3 depletion decreased the colocalization of γH2AX foci with RPA1, and thus, they might be involved in initiating DSB end resection for the recruitment of RAD51 to DSB sites at an early step in HR repair. These results show the novel underlying mechanism of the SIRT2 and SIRT3 functions in HR for genome stability Abstract : To examine the roles of SIRT2 and SIRT3 in DSB repair, I‐SceI‐based GFP reporter assays for DSB repairs were performed under SIRT2‐ or SIRT3‐depleted conditions. SIRT2 or SIRT3 depletion inhibited HR repair, but did not affect SSA and NHEJ repairs. Our results reveal the novel underlying mechanism of the SIRT2 and SIRT3 functions in HR for genome stability.